1995
DOI: 10.1080/02724936.1995.11747742
|View full text |Cite
|
Sign up to set email alerts
|

Human fetal exposure to ochratoxin A and aflatoxins

Abstract: Analysis of 64 cord blood samples from pregnant women in Sierra Leone revealed the presence of ochratoxin A (OTA) and aflatoxins in 25% and 58% of samples, respectively. Of the eight maternal blood samples collected during delivery, one contained OTA and aflatoxins were detected in six. There was no relationship between mycotoxins in maternal and cord blood. The effect these toxins might have had on the birthweight of infants is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 27 publications
2
33
2
Order By: Relevance
“…28 We found a highly significant negative correlation between aflatoxin levels in cord blood and birthweight and between maternal aflatoxin levels and birthweight. Unlike most reports in the literature, 9,29,30 we found a highly significant correlation between aflatoxin levels in mothers and their infants. This reflects either the speed and efficiency with which aflatoxins are transported across the placenta to the fetus or continuous ingestion of aflatoxin by the mother, thereby resulting in a steady supply of aflatoxin to the fetus.…”
Section: Discussioncontrasting
confidence: 85%
“…28 We found a highly significant negative correlation between aflatoxin levels in cord blood and birthweight and between maternal aflatoxin levels and birthweight. Unlike most reports in the literature, 9,29,30 we found a highly significant correlation between aflatoxin levels in mothers and their infants. This reflects either the speed and efficiency with which aflatoxins are transported across the placenta to the fetus or continuous ingestion of aflatoxin by the mother, thereby resulting in a steady supply of aflatoxin to the fetus.…”
Section: Discussioncontrasting
confidence: 85%
“…Other studies in the Gambia and Kenya found significant association between aflatoxin exposure and wasting (Okoth and Ohingo 2004). Four studies (Abdulrazzaq et al 2002;Abdulrazzaq et al 2004;Abulu et al 1998;Turner et al 2007) reported a negative correlation between birth weight and aflatoxin levels; two studies found this relationship only when the sex of the infant was female (Jonsyn et al 1995a;Vries et al 1989).…”
Section: Cgiar Agricultural Research On Food Safety and Aflatoxinsmentioning
confidence: 99%
“…There are several other studies of some note with respect to aflatoxin and birth outcomes with several showing significant negative correlations between birth anthropometry or child undernutrition and aflatoxin measures in biofluids [32–34, 38, 41, 42, 62, 133, 134], whilst one reported study found no statistically significant associations [135]. Importantly, this current set of studies used only “aflatoxin biomeasures” and none of these studies used validated exposure biomarker (AF-albumin in sera, AF-N7-Guanine in urine, nor AFM1 in urine) to assess the level of aflatoxin exposure; thus, quantitative relationships between the biomeasure and exposure outcome are not straightforward to interpret.…”
Section: Epidemiology Of Aflatoxin Driven Growth Falteringmentioning
confidence: 99%